Analysis of the dynamics of the land use changes in the Mediterranean region of southern Spain and its relationship with water availability - Sillero-Medina, José Antonio; Galacho-Jiménez, Federico Benjamín; Molina-Luque, Julián; Ruiz-Sinoga, José Damián (Wiley, 2024)
In the recent decades, the increase in irrigated agricultural areas has been a constant trend in the Mediterranean region, being concurrent with a reduction in the availability of water resources, due not only to an increase in demand but also to a reduction in supply as a result of the climate crisis. This study has analysed the evolution in land use changes between 1991 and 2021 in the Mediterranean region of southern Spain; the increase in the areas occupied by irrigated crops has been quantified; the climatic and edaphic dynamics linked to water risks have been identified, analysing the evolution of the annual precipitation, the number of rainy days and the distance to the wilting point of the soil; and, finally, it has been determined which factors are the most explanatory in this dynamic of land use. Using several machine learning methods, we could state how the current dynamics of land use are not in accordance with the availability and evolution of water resources, and how the areas where irrigated crops have increased the most are those where the climatic pattern shows a greater decrease in water resources, indicating how decisions on land uses are not done considering climatological conditions, but economic benefits.
Keywords: Suelo - Uso - Mediterráneo (Región); Suelo agrícola - Mediterráneo (Región); Agua - Abastecimiento agrícola - Mediterráneo (Región); Available water; Climate change; Irrigated crops; Land use changes; Machine learning; Mediterranean